2009
DOI: 10.5848/apbj.2009.00028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Perception(s) of Consumer Goods Packaging: Croatian Consumers Perspective(s)

Abstract: For centuries, packaging communicates and is capable of attracting consumer's attention. In the B2C market it usually communicates images influencing consumer perception, appeal to the consumer's emotions, and generate desire for some specific product. Therefore, packaging could be considered as promotional tool, especially within the retail industry environment. However, to understand how packaging communicates and influences consumers it is necessary to emphasize the way how consumers perceive packaging in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 8 publications
0
30
0
11
Order By: Relevance
“…A range of previous studies has examined how different sets of these aspects can influence consumers' choices, but studies including consumer perceptions of packaging are limited . Of the ones found, some examine consumer perceptions in relation to a limited set of predefined packaging‐related aspects; others focus strictly on the communicative function of packaging covering mainly the graphical design elements or focus on packaging material in particular …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A range of previous studies has examined how different sets of these aspects can influence consumers' choices, but studies including consumer perceptions of packaging are limited . Of the ones found, some examine consumer perceptions in relation to a limited set of predefined packaging‐related aspects; others focus strictly on the communicative function of packaging covering mainly the graphical design elements or focus on packaging material in particular …”
Section: Introductionmentioning
confidence: 99%
“…Although there appears to be a growing interest in packaging from an environmental perspective, previous research on consumers' environmental preferences for packaging is sparsely reported . In the studies found, consumer perception is examined in relation to predefined sets of environmental aspects of packaging that are mostly limited to matters of material and recyclability or are left unspecified . The authors of this study thus decided to broaden the environmental perspective of packaging from material and recyclability and explore how consumers spontaneously perceive packaging from an environmental perspective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shimp, 2003;Underwood, 2003;Draskovic, Temperley and Pavicic, 200) additionally suggest packaging material as a communicative element. As Fill (200) suggested, packaging communicates with consumers via its colour, shape, package size and the carried information.…”
Section: Communicative Dimensions Of Packagingmentioning
confidence: 99%